2020
DOI: 10.1021/acs.langmuir.9b03403
|View full text |Cite
|
Sign up to set email alerts
|

Long-Sought Redox Isomerization of the Europium(III/II) Complex Achieved by Molecular Reorientation at the Interface

Abstract: Redox-isomerism, i.e. the change of metal cation valence state in organic complexes, can find promising applications in multistable molecular switches for various 2 molecular electronic devices. However, despite a large amount of studies devoted to such processes in organic complexes of multivalent lanthanides, redox-isomeric transformations were never observed for europium. In the present work, we demonstrate the unique case of redox isomerization of Eu(III)/Eu(II) complexes on the example of Eu(III) doublede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…Thus, in the research works devoted to the study of this process on the example of sandwich-substituted cerium bis-phthalocyaninate [22], it was revealed that intramolecular electron transfer from the ligand to the lanthanide metal center and back (Figure 2a), i.e., reversible redox isomerization of the complex involving the multivalent Ce 3+/4+ cation, occurs when its solution is deposited on the water surface (Ce 4+ → Се 3+ ), and the subsequent compression of the thus obtained monolayer results in the reverse transition [13,22,[24][25][26][27]. Similar Eu 3+ ↔ Eu 2+ transitions for monolayers of donor-substituted europium bis-phthalocyaninates were described and unambiguously proved [23] (Figure 2b). Thus, in the research works devoted to the study of this process on the example of sandwich-substituted cerium bis-phthalocyaninate [22], it was revealed that intramolecular electron transfer from the ligand to the lanthanide metal center and back (Figure 2a), i.e., reversible redox isomerization of the complex involving the multivalent Ce 3+/4+ cation, occurs when its solution is deposited on the water surface (Ce 4+ →Ce 3+ ), and the subsequent compression of the thus obtained monolayer results in the reverse transition [13,22,[24][25][26][27].…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…Thus, in the research works devoted to the study of this process on the example of sandwich-substituted cerium bis-phthalocyaninate [22], it was revealed that intramolecular electron transfer from the ligand to the lanthanide metal center and back (Figure 2a), i.e., reversible redox isomerization of the complex involving the multivalent Ce 3+/4+ cation, occurs when its solution is deposited on the water surface (Ce 4+ → Се 3+ ), and the subsequent compression of the thus obtained monolayer results in the reverse transition [13,22,[24][25][26][27]. Similar Eu 3+ ↔ Eu 2+ transitions for monolayers of donor-substituted europium bis-phthalocyaninates were described and unambiguously proved [23] (Figure 2b). Thus, in the research works devoted to the study of this process on the example of sandwich-substituted cerium bis-phthalocyaninate [22], it was revealed that intramolecular electron transfer from the ligand to the lanthanide metal center and back (Figure 2a), i.e., reversible redox isomerization of the complex involving the multivalent Ce 3+/4+ cation, occurs when its solution is deposited on the water surface (Ce 4+ →Ce 3+ ), and the subsequent compression of the thus obtained monolayer results in the reverse transition [13,22,[24][25][26][27].…”
Section: Introductionsupporting
confidence: 54%
“…Thus, in the research works devoted to the study of this process on the example of sandwich-substituted cerium bis-phthalocyaninate [22], it was revealed that intramolecular electron transfer from the ligand to the lanthanide metal center and back (Figure 2a), i.e., reversible redox isomerization of the complex involving the multivalent Ce 3+/4+ cation, occurs when its solution is deposited on the water surface (Ce 4+ →Ce 3+ ), and the subsequent compression of the thus obtained monolayer results in the reverse transition [13,22,[24][25][26][27]. Similar Eu 3+ ↔Eu 2+ transitions for monolayers of donor-substituted europium bis-phthalocyaninates were described and unambiguously proved [23] (Figure 2b). The europium bis-phthalocyaninates, as well as most of trivalent lanthanide bisphthalocyaninates, in bulk solutions exist in neutral forms, where one macrocyclic ligand is in a formal dianionic state and another one is anion-radical-[(Pc 2− )Ln 3+ (Pc −• )] 0 .…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…In the framework of our ongoing projects, our investigations are focused on tetrapyrrolic compounds, namely porphyrins and phthalocyanines, and their synthetic modications and search for new types of applications. 17,[23][24][25][26][27][28][29][30][31][32][33] Recently, we developed synthetic strategies towards imidazole-and pyrazine-annulated porphyrins starting from tetrapyrrole dioxo-or diamino-derivatives and aromatic aldehydes. 28,[34][35][36][37][38] The sterically hindered tetrapyrrole was used as a synthetic platform for the development of bifunctionalized linear and angular annulated polyaromatic compounds, water soluble derivatives for biomimetic applications and macrocycles with terminal anchoring groups.…”
Section: Introductionmentioning
confidence: 99%